Cooperative cellular wireless networks - Hossain, Ekram, 1971-; Kim, Tong-in, 1958-; Bhargava, Vijay K., 1948- (Cambridge ; New York : Cambridge University Press, 2011)
"A self-contained guide to the state-of-the-art in cooperative communications and networking techniques for next generation cellular wireless systems, this comprehensive book provides a succinct understanding of the theory, fundamentals and techniques involved in achieving efficient cooperative wireless communications in cellular wireless networks. It consolidates the essential information, addressing both theoretical and practical aspects of cooperative communications and networking in the context of cellular design. This one-stop resource covers the basics of cooperative communications techniques for cellular systems, advanced transceiver design, relay-based cellular networks, and game-theoretic and micro-economic models for protocol design in cooperative cellular wireless networks. Details of ongoing standardization activities are also included. With contributions from experts in the field divided into five distinct sections, this easy-to-follow book delivers the background needed to develop and implement cooperative mechanisms for cellular wireless networks"--